Competitive supply chain management among non-identical suppliers under capacity constraint - Candeniz, Ozan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
A supply chain problem is considered that consists of a major manufacturer and two non-identical suppliers who supply a special product to the manufacturer. The aim of both suppliers is to work with the manufacturer by oﬀering better contract. One of the suppliers is large (possibly works for other manufacturers) and the other one is small (possibly works exclusively for the manufacturer). The market demand of the manufacturer is a known random distribution. By its infrastructure and experience, the big supplier has the production cost advantage compared to the small supplier. The manufacturer constitutes a small part of the business among the big supplier’s many customers while she is the main customer of the small supplier. Thus, the big supplier may not have an adequate capacity to satisfy the entire order from the manufacturer. For all practical purposes, it is assumed that the small supplier does not have a capacity restriction. In this study, all events are analyzed from the point of the big supplier, and how the equilibrium behavior of each player are examined when the production capacity of the big supplier is limited. For example, if the capacity of the big supplier is less than the optimal order quantity of the manufacturer to the small supplier, the big supplier does not oﬀer a contract to the manufacturer because of getting negative proﬁt. In other words, the manufacturer prefers to work with the small supplier. Moreover, while the expected proﬁt of the small supplier is equal to zero under full information, the small supplier gets a positive expected proﬁt (as information rent) when his production cost is private. Furthermore, the capacitated big supplier demands a premium because of information asymmetry on the processing cost of the manufacturer. However, this increases the wholesale price that the big supplier oﬀers to the manufacturer, so the big supplier faces the risk of losing the opportunity to work with the manufacturer.
Keywords: Business logistics.; Capacity theory (Mathematics)